2003
DOI: 10.1046/j.1344-3941.2003.00146.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in stress responses to transportation in goats: Effects of gonadal hormones

Abstract: The present study examined sex differences and the involvement of gonadal hormones in stress responses caused by road transportation in Shiba goats. In experiment 1, we investigated the stress responses of males and females to transportation. Plasma levels of cortisol (Cor) significantly increased during 1 h of transportation, and those in females were significantly higher than those in males. Plasma glucose (Glu) and free fatty acid (FFA) levels also increased similarly in both females and males by transporta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
22
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 29 publications
(41 reference statements)
3
22
0
Order By: Relevance
“…Although plasma Cor levels increase during road transportation in both male and female mature goats, those in males are significantly lower than those in females. We further demonstrated that the increase in plasma Cor levels during transportation was significantly reduced by 5α-dihydrotestosterone (DHT) in castrated male goats [1]. In addition, we have found that ovariectomized female goats show a similar response to DHT (unpublished data).…”
mentioning
confidence: 82%
See 4 more Smart Citations
“…Although plasma Cor levels increase during road transportation in both male and female mature goats, those in males are significantly lower than those in females. We further demonstrated that the increase in plasma Cor levels during transportation was significantly reduced by 5α-dihydrotestosterone (DHT) in castrated male goats [1]. In addition, we have found that ovariectomized female goats show a similar response to DHT (unpublished data).…”
mentioning
confidence: 82%
“…The first or the second group was used for the experiment between April-June or October-November, respectively. The detailed transportation procedure is described in our previous work [1]. Briefly, the experiment was performed as follows: On the day of the basal session (BS), in which animals were housed and fed as usual, 2 ml blood samples were collected at 9:00, 9:15, 9:30, 9:45, 10:00, 10:30, 11:00 and 13:00.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations